The factors that influence the purchase intention of plant-based meat among Gen Z in Malaysia - Chan, Yan Wen; Tong, Yi Ting (2024)
The increasing world population leads to higher meat consumption, impacting the environment negatively. PBM market grows due to global demand, especially in Malaysia where awareness of environment and health is increasing. Factors like middle-class vegetarians, healthconscious youths, and religious beliefs drive the popularity of PBM in Malaysia. PBM have great potential to become popular. For the food sector to meet customer demand, product innovation in PBM is crucial. This study looks at what influences Malaysian Gen Z's decision to buy PBM. Our study uses the Stimulus-Organism-Response (SOR) model to examine the factors influencing Gen Z Malaysia's desire to consume plant-based meat. The conceptual framework is rooted in the S-O-R model and consists of six factors, where attitude acts as a mediator (O) to clarify the cognitive mechanisms influencing consumer behavior. Through scrutinizing the interplay among environmental concerns, health considerations, and food safety as stimuli (S), alongside purchase intention as the behavioral response (R), our objective is to acquire insights into the decision-making dynamics of Malaysian Gen Z regarding PBM consumption. In this research, data from 385 Malaysian Gen Z respondents were gathered using questionnaires. SmartPLS software was employed to analyze data and build models to examine variable relationships. Findings show a notable connection between most hypotheses, except for the one concerning food safety and its effect on Malaysians' interest in PBM. This research contributes to improving comprehension of factors impacting Gen Z in Malaysia and promotes initiatives to increase the focus and Gen Z Malaysian customers' intention to purchase PBM.